Lukian z Samosat na temat krwawych rytuałów: diatryba O ofiarach - Osek, Ewa (Acta Universitatis Lodziensis. Folia Archaeologica, 2009)
This paper analyses the diatribe On sacrifices (De sacrificiis), written by famous Greek satirist of Roman imperial period, Lucian of Samosata (ca.120 – ca.190 A.C.), called Blasphemer or Atheist by Suda Lexicon, and traces its philosophical and literary sources. Lucian criticizes all forms of traditional Greek religion, in particular animal sacrifices (thysiai). He campaigns against traditional piety, that is, superstition, mentioning two pre-Socratic philosophers: Heraclitus of Ephesus and Democritus of Abdera. The satirical representation of Greek gods in On sacrifices bases on the Iliad of Homer, the desciption of the Eastern cults is anachronic (based on Herodotus), without any references to contemporary religious phenomena. The Lucian’s detailed description of religious animal slaughter (chapters 12-13), though it shows a great sensitivity and emotional involvement, is unclear, because there is no sign to recognize which he means: an usual Greek animal sacrifices or the holocausts. This emotional description is influenced by Homer’s poems and by two important moralizing writings: On piety (De pietate) by Theophrastus (fragments preserved in Porphyrius’ De ahstinentia, II) and On the eating the meat (De esu carnium, 1–II) by Plutarchus of Chaeronea.